Bali in the Covid-19 Pandemic: Population and Employment Dilemmas - I Gusti Wayan Murjana Yasa (Badan Riset dan Inovasi Daerah Provinsi Bali, 2020)
Purpose: The COVID-19 pandemic has a huge impact on the lives of Balinese citizens. The aim of this study is to find the right steps and frameworks that enable to reduce the spread and death caused by COVID-19 as quickly and as minimally as possible, so that the sustainable impact on the socioeconomic can be reduce. Research methods: Preventive measures are needed, especially for the Field Facilitator Staff as the front guard, so that the BSPS program channelled adequately. The key to smooth distribution, in addition to the precise mechanism, must also follow the government's recommendations and implement health protocols. Findings: The results show that the population and employment structure of Bali has high potential for the spread of the COVID-19 pandemic. This is due to the high level of population mobility, both population mobility between regions within the country and population mobility between countries. The second cause is the Balinese population structure consists of many elderly people, thus causing a high potential case fatality rate from a pandemic. Implications: Based on the results of the study, it is recommend minimize the possibility of the spread of covid-19 through the first and second rapid tests involving as many residents that potential to be covid-19 deployment carrier, both through local transmission and imported cases.